2016
DOI: 10.1177/0361684316662603
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Hazardous Drinking Among Racially and Socioeconomically Diverse Lesbian Women

Abstract: Lesbian women engage in more hazardous drinking than heterosexual women yet we know relatively little about what explains this disparity. In the present study, race, socioeconomic status, minority stress, general psychological processes and distress were examined as pathways to hazardous drinking among young (18-35 years) Black and non-Hispanic White lesbian women. We used the psychological mediation framework adaptation of minority stress theory and the reserve capacity model as theoretical underpinnings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 87 publications
(149 reference statements)
6
48
1
Order By: Relevance
“…No racial/ethnic differences were found in heavy episodic drinking (pastyear consumption of 4+ drinks in a day), alcohol problem consequences, or current marijuana use. In another online study of young adult women (ages 18 to 35), Lewis and colleagues [74] found that Black lesbian women reported significantly lower levels of hazardous drinking (based on AUDIT scores) than White lesbian women. MacCarthy and colleagues [75] examined substance use behaviors among Black women presenting for STI or HIV testing.…”
Section: Racial/ethnic Differences In Aod Usementioning
confidence: 99%
“…No racial/ethnic differences were found in heavy episodic drinking (pastyear consumption of 4+ drinks in a day), alcohol problem consequences, or current marijuana use. In another online study of young adult women (ages 18 to 35), Lewis and colleagues [74] found that Black lesbian women reported significantly lower levels of hazardous drinking (based on AUDIT scores) than White lesbian women. MacCarthy and colleagues [75] examined substance use behaviors among Black women presenting for STI or HIV testing.…”
Section: Racial/ethnic Differences In Aod Usementioning
confidence: 99%
“…Lesbian and bisexual women were the convenience sample of four more papers supporting the specific role of gender. Lewis et al 69 use Meyer's 4 and hatzenbuehler's 7 conceptualizations of minority stress to examine the associations between ethnicity, socioeconomic status, and minority processes in 867 lesbian women participating in an online survey. in line with the literature, they find that with the additive influence of ethnicity and socioeconomic status, distal minority stressors (i.e., perceived sexual minority discrimination) were associated with groupspecific processes (proximal sexual minority stress, concealment, lack of connection to the lesbian community) and psychological processes (rumination and social isolation) finally associated with negative mental health outcomes such as maladaptive coping and hazardous drinking behavior.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In previous analyses of these data looking specifically at race and SES, we found that race was not, but socioeconomic status (SES) was, related to increased perceptions of sexual minority discrimination. Among lesbian women, being Black was indirectly linked to more hazardous drinking but directly linked to less hazardous drinking (Lewis, Mason, Winstead, Gaskins, & Irons, ). Investigating the interplay of sexual identity, ethnicity, social class, ability status, and other statuses will increase our understanding of the paths from stigma‐related stress to alcohol problems and other health outcomes.…”
Section: Limitationsmentioning
confidence: 99%